2019
DOI: 10.5922/2079-8555-2019-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Russian soft power in the Baltic States through the lens of research: traditions, competition, confrontation

Abstract: In this article, we aim to analyse the research discourse in the Baltic countries (Estonia, Latvia, and Lithuania) as regards Russian soft power, which is considered as hard power, and to compare the theses that dominate this discourse with the actual interactions between Russia and the three states in media, education, and culture. Each Baltic country has built a system of political and legal restrictions to diminish the effect of Russian soft power, which is considered in terms of hard power, i.e. as a threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On the contrary to above research studies, some authors [ 57 , [72] , [73] , [74] ] found that education does not contribute to build soft power when there are wide political and cultural differences between countries. For instance, by conducting research on Chinese international students studying in western countries, Bislev [ 57 ] analyzed that existing studies do reveal that educational exchange programmes can promote the creation of soft power under certain circumstances, but some of these conditions are problematic to meet in the case of Sino-Western educational partnership.…”
Section: Resultsmentioning
confidence: 79%
“…On the contrary to above research studies, some authors [ 57 , [72] , [73] , [74] ] found that education does not contribute to build soft power when there are wide political and cultural differences between countries. For instance, by conducting research on Chinese international students studying in western countries, Bislev [ 57 ] analyzed that existing studies do reveal that educational exchange programmes can promote the creation of soft power under certain circumstances, but some of these conditions are problematic to meet in the case of Sino-Western educational partnership.…”
Section: Resultsmentioning
confidence: 79%
“…Parents were afforded the choice to enroll their children in either Russian or non-Russian schools, with Russian being a mandatory subject in the latter, while in Russian-language schools, the native languages of the Baltic peoples were offered as optional courses. This educational policy engendered significant discontent among the Baltic populace (Vorotnikov & Ivanova, 2019).…”
Section: 22mentioning
confidence: 99%
“…The pro-Russian information is disseminated in Estonia and other EU countries by the Russian state and state-related media and even global media including international news agencies and domestic news media and is considered by Russia as form of its soft power (Vorotnikov & Ivanova, 2019 ;Wagnsson & Barzanje, 2019;Watanabe, 2017). According to the "Foreign Policy Conception of the Russian Federation" soft power "primarily includes the tools offered by civil society, as well as various methods and technologies -from information and communication to humanitarian methods and other types of technologies" (The Ministry of Foreign Affairs of the Russian Federation, 2016 , II, 9).…”
Section: Introductionmentioning
confidence: 99%